Analysis of signal to noise and directivity characteristics of das VSP at near and far offsets-A CO2CRC Otway Project data example - Correa, Julia; Egorov, Anton; Tertyshnikov, Konstantin; Bona, Andrej; Pevzner, Roman; Dean, Tim; Freifeld, B.; Marshall, S. (Society of Exploration Geophysicists, 2017)
© 2017 by The Society of Exploration Geophysicists. During the last decade, distributed acoustic sensing (DAS) has emerged as a new technology for seismic acquisition. DAS has the potential to reduce the cost of permanent monitoring operations over time as it offers long equipment survivability and requires minimum maintenance. However, broad adoption of DAS technology still faces some challenges, such as low sensitivity and high levels of noise compared to conventional seismic sensors. Recent developments in fiber-optic systems and cable designs aim to overcome these limitations. To understand how DAS can be used in monitoring applications, it is important to know how it behaves with varying offsets and incidence angles. An offset VSP survey was acquired, at the CO2CRC Otway Project, using a straight single-mode fiber, a straight "enhanced-backscatter" fiber, and a conventional three-component geophone tool. The results from this survey show that DAS has the potential to provide similar, or even superior, quality data sets as conventional geophones.